The impact of urban development on social capital in urban fringe area of Bangkok, Thailand - P. Iamtrakul; I. Raungratanaamporn; J. Klaylee (International Association of Lowland Technology, 2018)
Rapid development in center core of urban area motivates people from rural migrates to urban for reaching better quality of life. However, due to the hindsight between development planning and policies, and tangible development causing negative impacts on several dimension of urban living which includes increasing social isolation, unsafe condition and auto-dependency. This situation has affect social capital on both individual and communities level. Therefore, the aims of this study are (1) to identify the set of variables that influence on social capital formation in suburban area; (2) to determine the component factors that formulate social capital value in variety context of urban development; and (3) to analyze relationship among physical factors together with nonphysical ones for examine its effects. This study selected Thakhlong Municipality as a study area to perform spatial analysis for investigating different typology of social capital value among a variety group of residents disperse in urban fringe of commuter town character. Results from this study demonstrated that the formulation of social capital values influenced by the integrating effect of both physical characteristics of building agglomeration and social perspectives which was stimulated by land use policy and planning.